THE LEVEL OF SOCIAL MEDIA INFLUENCES ON CYBER HARASSMENT AGAINST WOMEN - Abdul Rahman Abdul Manaf; Fauziah Ismail; Kumuthashni Shanmugam; Tengku Kastriafuddin Shah Tengku Yaakob; Zuraidi Ahmad Mokhdzar, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
In general, social media has been seen to be beneficial to society and women but with the improvement of technology today women are now exposed to great danger. This problem has been proven by the United Nations, stated that 73 percent of women and girls have been exposed to or experienced some form of online violence formerly known as cyber-disruptions. According to Cyber Security Malaysia's statistics, 300 cyber-disruptions have been recorded in 2012 and increased to 529 cases in 2016. Cyber bullying among students is increasingly dangerous as 250 cases have been filed in 2012 and rose to 338 cases last year. Overall, 1524 cyber bullying cases have been recorded over the last five years (Vijaindren, 2017). The number of statistics recorded by the Malaysian Computer Emergency Response Team (MyCERT) in 2018 stated that 80 cases of cyber bullying from January to March were filed and most importantly all victims were identified as women. However, this phenomenon leads to social disorders such as cyber disorders especially among female consumers. Disorders include various types of offensive or unwanted behaviours to make others uncomfortable especially in women. It is an unlawful form; discrimination and all human rights law prohibits this act but the disruption ratio continues to rise despite the law being present in our society. Consequently, these research objectives were to identify the level of social media’s influences, level of cyber harassment and to analyze the relationship between influences of social media against cyber harassment among women in Ipoh, Perak. This quantitative research has conducted using questionnaire distribution to 200 respondents using Stratified Random Sampling (SRS) and Simple Random Sampling (SRS). This research result found that the correlation test showed influences of social media and cyber harassment on women has a significant strong relationship (r=0.993, p<.01). This positive relationship demonstrates high level of social media influences contribute to high level of cyber harassment against women and vi-versa. The top mean score for the level of cyber harassment against women on social media are respondents agree that they have received dirty joke while interacting on social media (m=4.07). Meanwhile, the highest mean score for influence’s level of social media against women are respondents strongly agrees that the attention they get from posting on social media websites makes them feel good (m=4.16). The result from the research is vital due to technology eruption whereby most of the people are exposed to the digital technology including social media. This research reveals that sexual violence related with social media is a visible where prevention action should to be taken for getting decrease the issue. All parties include individual, Non-Government Organization (NGO), authority and society also take into consideration as a whole responsibility to overcome cyber harassment issue in the country. Therefore, intensive efforts such as enforcement of technology abuse or misuse and fostering ethical education awareness to facilitate people wisely use social media without any bad threats to women should be considered.